Surgical Management of the Sphenoid wing meningiomas - Khattak, Azmatullah; Haider, Ali (Journal of Postgraduate Medical Institute, 2011)
to find outcome of total removal of sphenoid wing meningioma. This study was conducted at the department of Neurosurgery LRH, peshawar from 15th August, 2002 to 15th August 2005. Only patients of sphenoid wing meningiomas were included in this study. Patients above 70 years who were not fit for general anaesthesia were excluded. all patients were operated through pterional approach. follow up was done till discharge from hosptial or death of the patients. Data was collected regarding preoperative and postoperative findings of the patients for final analysis. early diagnosis and total removal of tumour improves the clinical status. chronic headache, slow mentation and seizures needs attention and early computerized tomography scan of the brain with contrast.